Eksistensi Pondok Pesantren Syahamah Putri Dalam Menjaga Paham Ahlusunah Waljamaah di Kecamatan Margoyoso Kabupaten Pati Provinsi Jawa Tengah - Rahmawarni Harahap; Hasan Bakti Nasution; Mohammad Al Farabi (Dinasti Review, 2024)
This study aims to analyze the curriculum, kiai and teacher strategies, and describe the contribution of Pondok Pesantren Syahamah Pati Putri in maintaining the understanding of Ahlusunah Waljamaah to the community in Margoyoso sub-district, Pati district, Central Java province. This research was conducted using field research method with qualitative approach. Research instruments through observation, interviews and document studies. The data sources of this research are primary and secondary data sources obtained from Syahamah Pati Putri Islamic Boarding School in Margoyoso sub-district, Pati district, Central Java province. The results showed that the curriculum applied at Syahamah Pati Putri Islamic Boarding School adheres to the salaf manhaj by being guided by the turats books which include religious science and Arabic language materials, such as tawhid, fiqh, morals / Sufism, nahu, saraf, and Al-Qur'an. The strategy of the kiai/leader of the hut in maintaining Ahlusunah Waljamaah understanding is to equip students with